Work-life Balance and Compensation on Performance with Job Satisfaction as an Intervening Variable for Millennial Generation Banking Employees - Ingsih, Kusni; Budiantoro, Risanda Alirastra; Hasanatina, Foza Hadyu; Ali, Shujahat (Jurnal Manajemen Bisnis, 2022)
Research aims: The research aims to determine the effect of work-life balance and compensation on performance with job satisfaction as a variable intervening of millennial generation banking employees in Semarang City.Design/Methodology/Approach: This research design is quantitative. This study’s primary data was obtained by distributing questionnaires to millennial-generation banking employees. The study was conducted for one month. Hypothesis testing in this study used the SEM-STATA method.Research findings: With the object of research being the millennial generation working in the banking industry in Semarang City, compensation and work-life balance positively correlated with employee performance. The results also confirmed the role of the intervening variable, job satisfaction, in the relationship between work-life balance and compensation on employee performance. Theoretical contribution/Originality: The findings supported the existing theories (Spillover Theory, Enrichment Theory, and Equity Theory).Practitioner/Policy implication: For banking companies to pay attention to employee well-being because compensation will satisfy and motivate employees and improve work performance. It is also reasonable for the company to provide job satisfaction to employees to improve employee performance. To enhance the performance of banking employees for the millennial generation in the future through increasing programs that support employees to harmonize their personal lives and work activities to have a relationship with employees’ job satisfaction.Research limitation/Implication: The subject is limited to Millennial Generation and does not capture other generations, such as Baby Boomer and Generation X. It would be better if future researchers could analyze the different characteristics and personalities in the workplace. This paper also only tested the model by Millennial Generation who work in the banking industry in the Semarang City area. It cannot be generalized to other sectors and regions.